2006
DOI: 10.3354/meps323263
|View full text |Cite
|
Sign up to set email alerts
|

Spatial separation of foraging habitats among New Zealand fur seals

Abstract: We studied the foraging behaviour of lactating female, adult male and juvenile New Zealand (NZ) fur seals to compare and contrast their foraging strategies and assess the degree of spatial separation of their foraging habitats. Adult male fur seals are longer and heavier than lactating females, which are longer and heavier than juveniles. Trip duration was positively correlated with the distance travelled by all age/sex groups. Juveniles conducted longer trips and travelled further from the colony than males. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
72
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(77 citation statements)
references
References 39 publications
5
72
0
Order By: Relevance
“…To remove erroneous locations, datasets were also filtered based on a maximum transit rate of 2 m s -1 using the algorithm described in Freitas et al (2008). Since all other location qualities (3, 2, 1, 0, A, B) were retained for filtering, the transit rate of 2 m s -1 was chosen as it is equal to or more stringent than previous studies tracking fur seals or sea lions (3 m s -1 , Bailleul et al 2005, Ream et al 2005, Melin et al 2008; 2.8 m s Page et al 2006). This strict filtering requirement was selected in order to retain the highest number of positions yet ensure positions with large error were removed.…”
Section: Animal Handling Research Was Conducted Frommentioning
confidence: 99%
“…To remove erroneous locations, datasets were also filtered based on a maximum transit rate of 2 m s -1 using the algorithm described in Freitas et al (2008). Since all other location qualities (3, 2, 1, 0, A, B) were retained for filtering, the transit rate of 2 m s -1 was chosen as it is equal to or more stringent than previous studies tracking fur seals or sea lions (3 m s -1 , Bailleul et al 2005, Ream et al 2005, Melin et al 2008; 2.8 m s Page et al 2006). This strict filtering requirement was selected in order to retain the highest number of positions yet ensure positions with large error were removed.…”
Section: Animal Handling Research Was Conducted Frommentioning
confidence: 99%
“…The finding that foraging trip duration was positively related to the total and maximum distance travelled from the colony is common in studies of marine central-place foragers (Harcourt et al 2002, Page et al 2006). Individual differences in foraging trip length (distances or duration) may result from variations in prey availability and/or prior knowledge of where prey aggregations exist.…”
Section: Foraging Behaviour and Distancementioning
confidence: 99%
“…Central-place foragers commonly use areas where patches of prey are aggregated by physical factors (Guinet et al 1997, Awkerman et al 2005, Simmons et al 2007) and/or elevated levels of primary productivity (e.g. chl a) (Hyrenbach et al 2002, Weimerskirch et al 2004, Page et al 2006, Suryan et al 2006. Previous analyses of chlorophyll data collected from Sea-viewing Wide Field-of-view Sensors (SeaWifs) in southern Gulf St Vincent indicated that levels of primary production (chl a) increase 2-fold over the austral summer (~0.4 mg m -3 for October versus 0.8 mg m -3 for February, Petrusevics 2008).…”
Section: Foraging Behaviour and Habitatmentioning
confidence: 99%
“…Additionally, young animals may have different nutritional requirements, insufficient experience, or may be avoiding competition with older conspecifics (Fowler et al 2006). Shifts in diet or changes in foraging/diving behaviors with increasing age have been observed in other otariid pinnipeds including the Galápagos fur seal (Arctocephalus galapagoensis; Horning & Trillmich 1997), New Zealand fur seal (A. forsteri; Page et al 2006), Australian sea lion (Neophoca cinerea; Fowler et al 2006), Steller sea lion (Eumetopias jubatus; Raum-Suryan et al 2004, Pitcher et al 2005, and California sea lion (Zalophus californianus; NMML unpubl. data).…”
Section: Age-class Variationmentioning
confidence: 99%